Attracting Public with the Speaking Proficiency: Improving Formal Master Ceremony Skill for Teachers: Memikat Publik dengan Kemahiran Berbicara: Meningkatkan Keterampilan Pembawa Acara Formal bagi Guru - Syafruddin; Refisa Ananda; Rahma Dewi Hartati; Murni Maulina; Ratu Badriyah; Mohammad Yunus; Teguh Prakoso (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Effective speaking skills are a crucial aspect in the world of education, especially for teachers as learning facilitators. However, there is a problem in terms of the lack of speaking skills that can attract the attention of the public and students in the class. This Community Service aims to overcome this problem by organizing formal emcee training for teachers. The solving method is carried out through intensive training that focuses on developing persuasive speaking skills, setting clear presentation structures, and increasing confidence when speaking in public. The training involves the active participation of teachers who wish to improve their speaking skills. The results of the service activities showed a significant increase in the speaking skills of the teachers after attending the training. They are able to captivate the public's attention with an attractive presentation style, deliver messages more effectively, and maintain positive interactions with listeners. In addition, the teachers also experienced an increase in self-confidence when appearing in public. In conclusion, formal presenter training is an effective method of improving speaking skills for teachers. Public speaking skills help create a more interactive learning environment and inspire students. It is hoped that the development of speaking skills will have a positive impact on the learning process and enhance the school's reputation in the educational community.